String Gas and Brane Gas Developments - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will first describe a simple generalization of the previously defined string gas cosmology, namely brane gas; and then we will calculate the spectrum of scalar and tensor perturbations in string gas cosmology.